Analisis Kepatuhan Hukum Masyarakat Desa Kunti Kecamatan Bungkal Kabupaten Ponorogo Dalam Membayar Pajak Bumi Dan Bangunan: . - Wigati, Pipit Kalsum (Institut Agama Islam Negeri Ponorogo, 2024)
Acceptance from the taxation sector remains the primary source of government spending, both at the central and local levels. However, there are still many issues in tax collection itself. Taxpayer compliance in paying Property Tax (PBB) can facilitate local governments in implementing development in their regions. However, in reality, taxpayer awareness in Indonesia is still generally low. Many villages still have taxpayers who are not tax-compliant. Unlike other villages, in Kunti village, the majority of the population is already tax-compliant, as evidenced by the predicate awarded to Kunti village as a Tax-compliant village for 2 consecutive years. With the level of compliance found in Kunti village, it is hoped to serve as an example for other villages where taxpayer awareness is still low. This research is qualitative in nature, employing field research with a descriptive approach. Data collection techniques include interviews and documentation. The analysis method used in this research is empirical. From the results of this research, it is known that the level of land and building tax compliance in Kunti village from 2021 to 2023 is very satisfactory. The compliance of the community in Kunti village cannot be separated from the role of the village government, which directly participates in the collection of land and building taxes. The role of the Kunti village government itself in increasing legal compliance among its community is through regular socialization, improving services in tax collection, and giving rewards to compliant taxpayers. With the active role played by the Kunti village government, compliance among its community in paying land and building taxes has been increased.